HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BALITA DI PUSKESMAS SUNGAILIAT KABUPATEN BANGKA TAHUN 2020 - Izzati Sabila; T Marwan Nusri; Dita Fitriani; Astri Pinilih (SPIRAKEL, 2021)
Acute Respiratory Infection (ARI) is an acute infection of the upper or lower respiratory tract caused by a virus or bacteria that lasts for 14 days. In Indonesia ARI still a problem because of environmental factors and behavior. As mention in H.L Blum’s classical theory that environment is the most influenced factor for the health status. The physical environment of the house includes the condition of clean water facilities, the condition of latrines, and the area of ventilation. This research aims to find out the effect of the physical environment of the house on the incidence of ARI in children under five at Sungailiat Health Center for the period October - December 2020. This research is a type of correlational analytic survey research with a cross sectional design. The population in this study were 118 toddlers aged 12-59 months. The sample in this study was 60 toddlers who were taken using simple random sampling technique. The statistical test used the chi-square test using the SPSS version 23 program. The results showed that there was no relationship between the condition of clean water facilities (p = 0.115), latrine conditions (p = 0.389), room ventilation area (p = 0.109) and the incidence of ARI. So it can be concluded that there is no relationship between the physical environment of the house and the incidence of ARI in children under five.